A review on H2 production through photocatalytic reactions using TiO2/TiO2-assisted catalysts. (15th May 2018) - Singh, Rohini; Dutta, Suman
Highlights: Synthesis of nano-TiO2 with large surface area. Modified structural, morphological, and optical behavior of TiO2 nanoparticles. Synthesis of nano-TiO2 with a band gap suitable for solar activation. nano-TiO2 can be used for wastewater treatment and solar hydrogen production. Abstract: Photocatalytic water-splitting technology by using nano-sized TiO2 can produce low cost and environment-friendly hydrogen using renewable resource such as solar energy, which can fulfil the future requirements of energy. Nano-sized TiO2 is highly efficient as a semiconductor photocatalyst possessing high surface area. The significant drawbacks of utilising TiO2 as photocatalysts are reduced absorption capacity of visible radiation and fast recombination of photoexcited electron/hole (e − /h + ) pair. Its activity is restricted to UV light, which is only ∼3–5% of the solar spectrum. This present review elucidates various aspects and the recent researches related to TiO2 nano photocatalysis for the effective solar hydrogen generation via photocatalytic water splitting technology.